2020
DOI: 10.1002/14651858.cd012906.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin monotherapy for adults with type 2 diabetes mellitus

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of metformin monotherapy in adults with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 151 publications
1
16
0
3
Order By: Relevance
“…Metformin (1,1-dimethyl biguanide hydrochloride) (MF), an orally administered biguanide, is a first-line drug for the treatment of type 2 diabetes mellitus (T2DM). It reduces the adipose tissue mass and increases the tissue sensitivity to insulin, thereby reducing hyperglycemia, normalizing carbohydrate and lipid metabolism and preventing inflammation and oxidative stress in the tissues [ 1 , 2 ]. MF is also used to treat non-alcoholic fatty liver disease [ 3 ], coronary artery disease [ 4 , 5 ], acute kidney injury and chronic kidney disease [ 6 ], in patients with T2DM, metabolic syndrome (MetS) and obesity, and in patients without apparent symptoms of metabolic disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin (1,1-dimethyl biguanide hydrochloride) (MF), an orally administered biguanide, is a first-line drug for the treatment of type 2 diabetes mellitus (T2DM). It reduces the adipose tissue mass and increases the tissue sensitivity to insulin, thereby reducing hyperglycemia, normalizing carbohydrate and lipid metabolism and preventing inflammation and oxidative stress in the tissues [ 1 , 2 ]. MF is also used to treat non-alcoholic fatty liver disease [ 3 ], coronary artery disease [ 4 , 5 ], acute kidney injury and chronic kidney disease [ 6 ], in patients with T2DM, metabolic syndrome (MetS) and obesity, and in patients without apparent symptoms of metabolic disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other aspects of the design have been criticised (4) and in addition, recent meta-analysis could not replicate the cardiovascular benefit of metformin reported in UKPDS, although other included trials were smaller with shorter follow up (5,6). A recent Cochrane Library systematic review concluded that there was no clear evidence whether, compared with no intervention, behaviour changing interventions, or other glucose-lowering drugs, metformin monotherapy influences patient-important outcomes (7). Metformin is generally well-tolerated although up to a third of patients are unable to tolerate gastro-intestinal side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, the most prescribed biguanide in the present study, is effective, inexpensive and might reduce the risk of cardiovascular events and death; however, evidence has not been fully established regarding the effects of metformin on patient‐important outcomes 27 . Ideally, head‐to‐head large‐scale, long‐term randomized controlled trials should be carried out to clarify which medication is efficacious for glycemic control and to prevent complications, especially among East Asian populations.…”
Section: Discussionmentioning
confidence: 98%